The Translation of Philosophical Texts: Between Literature and Science (Castilla. Estudios de Literatura, 2015)
In this paper we study the translation of philosophical texts. These texts are marked by their deeply ideological character and a nature and function that place their cross-lingual transfer between the literary and the scientific translation. Our objective in this context is to obtain a clear and comprehensive understanding of the historical and cultural importance of the translation of this discursive class, of its definition, its typology and its translational difficulties, with special reference to the problems posed by terminology, due to the fact that this kind of texts combine features of literary and scientific languages.
Keywords: translation; philosophical text; philosophy; literature; science